Physiological and molecular responses of two contrasting drought resistance pistachio interspecific hybrid rootstocks - Osku, Mozhdeh; Procino, Silvia; Mascio, Isabella; Miazzi, Monica Marilena; Vivaldi, Gaetano Alessandro; Vona, Danilo; Fanelli, Valentina; Roozban, Mahmoud Reza; Sarikhani, Saadat; Arab, Mohammad Mehdi; Akbari, Mohammad; Vahdati, Kourosh; et al. (Frontiers in Plant Science, 2025)
Pistachio (Pistacia vera L.) is a valuable nut crop that faces significant challenges due to drought stress, which can severely impact its growth, yield, and quality. Understanding the physiological and molecular mechanisms underlying drought tolerance is crucial for developing resilient pistachio rootstock. In this study, among nine-month-old saplings of seven clonal interspecies hybrids of Pistacia atlantica × Pistacia integerrima, two contrasting hybrids, ‘C4-2’ (sensitive) and ‘C9-4’ (resistant), were assessed for their morphological, physiological and molecular responses to 30 days of withholding irrigation. Water withholding induced alterations in root architecture in the resistant clone, accompanied by an increase in compatible solutes, including glycine betaine, proline, and total soluble carbohydrates. Enzyme activities of guaiacol peroxidase (GPX) and catalase (CAT) were elevated in the resistant clone under water stress. Both clones exhibited increased levels of malondialdehyde (MDA) and hydrogen peroxide (H2O2) during the stress period, with these changes being more pronounced in C4-2 compared to C9-4. In the resistant clone, both CDPK and ZEP genes were upregulated, suggesting their role in enhancing stress signaling and osmotic regulation under drought stress. The upregulation of CDPK indicates its involvement in calcium-mediated signaling pathways, which likely contribute to improved drought tolerance. Similarly, DHN expression was strongly influenced by CDPK activity, further emphasizing its role in maintaining cellular integrity during stress conditions. The findings provide valuable insights for developing more resilient pistachio rootstocks capable of thriving in water-limited environments. Specifically, C9-4 demonstrated significant drought tolerance in this study. Nonetheless, further research is necessary to validate the broader applicability of these findings and to evaluate its performance across various stress environments.